Intrinsic and extrinsic tensions in the SENCo role: navigating the maze of 'becoming'. Issue 4 (15th September 2022) - Kay, Virginia; Chrostowska, Marlena; Henshall, Amanda; Mcloughlin, Anne; Hallett, Fiona
Abstract : The purpose of this narrative literature review is to provoke new ways of understanding the plethora of research around the role of the SENCo. Specifically, the aim is to use four themes as lenses to explore how SENCo identities are formed, and reformed, by intrinsic and extrinsic motivators. The four themes have been distilled from a list of standards that underpin the learning outcomes of the National Award for Special Educational Needs Coordination in England and are: change; culture; influence; and challenge. Although these themes stem from a given place and time, they mirror policy directives, and subsequent practice, across national boundaries and are visible in much of the research around the SENCo role and its equivalent. Whilst each of the themes is considered individually, areas of overlap are identified enabling both a focused, and wholesale, view of the literature in order to highlight areas of opportunity, conflict and tension that serve to shape SENCo identity.